Reprobada por la moral la censura católica en la producción literaria durante la posguerra - Pérez del Puerto, Ángela (La Casa de la Riqueza. Estudios de la Cultura de España, 2021)
This book is an analysis of the literary censorship that Acción Cató?lica (AC) implemented in Spain, through the Secretariat of Bibliographic Orientation (SOB) during the 1940s. The text delves into this system of trial and cultural control to demonstrate that AC imposed its own ideology on its members, redefining literature until turning it into another tool of its social indoctrination. As a consequence, it is demonstrated that AC questioned? the discursive authoritarianism of the Franco regime and, based on the work of literary criticism and the analyzed censor reports, a new perspective is provided from which to reconsider the relationship between Catholicism and the dictatorship. The study of the disagreements and ideological conflicts that arose within the regime reveals the existence of differentiated discourses in both institutions, thus breaking the illusion of homogeneity and apparent harmony. The work is presented as a novel approach to the strategies of cultural repression adopted by the dictatorship and the Church in the postwar period that opens an alternative door for the analysis of the mechanisms of intellectual and social control in that period and, in addition, it connects the existing bibliography about the changing and complex nature of Francoism with cultural studies.